2016
DOI: 10.1080/19476337.2016.1245678
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some physical and chemical characteristics of buckwheat (Fagopyrum esculentum Moench) grains

Abstract: Several physical and chemical characteristics of two buckwheat varieties (commercial buckwheat and the Güneş variety) were determined and compared in terms of linear dimensions, length, width, thickness, arithmetic and geometric mean diameters, sphericity, surface area, aspect ratio, volume, weight of thousand grains, bulk and densities, porosity, terminal velocity, angle of repose, coefficient of static friction, rupture strength, apparent colour of buckwheat varieties, ash, protein, antioxidant capacity, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
4
19
3
2
Order By: Relevance
“…Sample BU4, being high in starch, had the lowest protein content (13.9 g/100 g dm) among the buckwheat samples. Unal et al [ 46 ] also found a protein content of 13.8 g/100 g dm. For the other buckwheat samples, the amount of proteins varied between 14.4 and 16.4 g/100 g dm, which is within the range of results from other studies (14.0–17.9 g/100 g dm) [ 14 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample BU4, being high in starch, had the lowest protein content (13.9 g/100 g dm) among the buckwheat samples. Unal et al [ 46 ] also found a protein content of 13.8 g/100 g dm. For the other buckwheat samples, the amount of proteins varied between 14.4 and 16.4 g/100 g dm, which is within the range of results from other studies (14.0–17.9 g/100 g dm) [ 14 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Iron ( Fe ), copper ( Cu ), zinc ( Zn ), manganese ( Mn ), and boron ( B ) in the extracts were analyzed using inductively coupled plasma optical emission spectrometry (ICP‐OES) (Perkin Elmer OPTIMA 2100 DV). The samples were analyzed in three replications (Unal, Izli, Izli, & Asik, ).…”
Section: Methodsmentioning
confidence: 99%
“…The weight (W) was determined with an OHAUS Analytical Balance. The weight of 100 peas was used to extrapolate the weight of 1000 grains, recording the results in grams (Unal et al, 2017). The bulk density was determined according to Equation 4 (Singh & Goswami, 1996).…”
Section: Physical Properties Of the Grains Dried With The Appropriatementioning
confidence: 99%